Sosialisasi Tentang Sistem Pemerintahan Adat Yapio Patai di Elpaputih, Kabupaten Seram Bagian Barat - Pietersz, Jemmy Jefry; Picauly, Benjamin Carel; Saija, Vica Jillyan Edsti; Kuahaty, Sarah Selfina (Faculty of Law Pattimura University, 2024)
Introduction: On Seram Island, there is an association of customary law communities who live in groups in a certain form, known in the Wemale language as